Encapsulation of stilbazolium-type dyes into layered metal–organic frameworks: solvent-dependent luminescence chromisms and their mechanisms. Issue 5 (2nd April 2019) - Zhao, Li-Ming; Shen, Xia-Qiang; Tan, Li-Ting; Zhang, Wen-Ting; Song, Kai-Yue; Jiang, Rong; Li, Hao-Hong; Chen, Zhi-Rong
Abstract : Dye@Cd-LMOCs composites exhibit interesting solvent-dependent chromismic fluorescence, in which a two step solvent exchange process and a new electron transfer route are proposed. Abstract : The incorporation of organic dyes into host matrices has attracted great interest for developing new functional materials. In this work, two Cd-based layered metal–organic complexes (Cd-LMOCs), i.e. [Cd3 (BTB)2 (DEF)4 ] n, (1-DEF ) and [Cd3 (BTB)2 (DMF)4 ·2DMF] n, (2-DMF ), were synthesized, and three different organic stilbazolium-type dyes were incorporated into the layered Cd-LMOCs: CMAS +, which contains an electron-withdrawing group (–CN) on the amine, and DAST + and HMAS +, which contain electron-donating groups (–CH3, –OH) on their amines. Interestingly, solvent-dependent luminescence chromisms were observed; these only occurred in DMA solvent. The dye@Cd-MOC composites obtained from DMA solvent have been fully characterized by IR, UV-Vis, PXRD, SEM, TEM and TGA; they exhibit blue-shift photoemissions and enhanced quantum yields compared with the pristine Cd-LMOCs and dye samples. After loading with dyes, the photocurrents were diminished by 2 to 6 times. Based on a combination of experimental and theoretical simulations of the dye@Cd-LMOC systems, a two-step solvent-dependent chromism mechanism was proposed: solvent exchange reactions occur firstly, and the dyes then enter the Cd-LMOCs via direct or semi-coordinated bonds between the Cd centers and guest dyes. Specifically, (CMAS)I@1-DMA with direct Cd–N bonds exhibits the highest quantum yield, and a new electron transfer route from the metal centers of the host skeletons to the side groups of the guest dyes has been found. In all, the introduction of electron-withdrawing groups on dyes is beneficial for host–guest interactions.